Amino acid-based ionic liquids as dual kinetic-thermodynamic methane hydrate inhibitor - Masri, A.N. (Elsevier B.V., 2022)
Three amino acid-based ionic liquids (AAILs) are synthesized to evaluate their performance as inhibitors. They are 1-ethyl-3-methyl-imidazolium-glutamate (EMIMGlu), 1-(3-cyanopropyl)-3-methyl-imidazolium-glutamate (CPMIMGlu) and 1-butyl-3-methyl-imidazolium-glutamate (BMIMGlu). The structures are clarified using Nuclear Magnetic Resonance. Evaluation of their methane hydrate inhibitor performance is performed by micro-differential scanning calorimeter at 5â15 MPa. As a baseline, the hydrate dissociation in water is also evaluated. A standard correlation of methane hydrate dissociation in water is successfully developed with a low average absolute error. Additionally, the AAILs behave as both thermodynamic (THI) and kinetic (KHI) hydrate inhibitors. They simultaneously shift the HLVE curve to a lower temperature and decelerate the hydrate formation by reducing the hydrate nucleation rate. EMIMGlu shows the highest THI performance by producing an average temperature shift of 1.14 K, followed by CPMIMGlu (0.91 K) and BMIMGlu (0.87 K). Furthermore, the addition of the nitrile group in CPMIMGlu IL has enhanced the kinetic inhibition process. The kinetic inhibition performance represented by the relative inhibition power (RIP) decreases in the trend of CPMIMGlu (1.31), EMIMGlu (1.30) and BMIMGlu (0.063). The mechanism of the inhibition is further studied by utilizing COSMO-RS software through Ï-profile and Ï-potential to understand the inhibition process at the molecular level. The experimental results and computational studies reveal that AAILs behave as THI and KHI through the existence of four oxygen atoms in their anions and cyano group in the CPMIM cation. Thermodynamic inhibition properties of AAILs are found to be influenced by the polarity of AAILs while the kinetic inhibition properties of AAILs are found to be influenced by the hydrogen-bonding acceptor value of the AAILs. Â© 2022 Elsevier B.V.